Persepsi Auditor Eksternal Atas Pengaruh Kemudahan dan Kegunaan Artificial Intelligence Terhadap Kualitas Audit - Yetri Martika Sari; Rosydalina Putri (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
This study aims to investigate external auditors' perception of the impact of artificial intelligence's ease of use and usefulness on audit quality, while also examining the potential scepticism among external auditors towards the integration of artificial intelligence in the audit process. A quantitative approach is utilized to analyze the relationship between the variables. The research was conducted through questionnaires distributed via telegram and WhatsApp groups, email, and collaboration with IAPI. One hundred and eight valid responses were gathered from external auditors of Big Four KAP, internationally affiliated KAP - non big four, and national KAP. Findings reveal that external auditors do not exhibit a sceptical attitude towards the usage of artificial intelligence in the audit process. The test results demonstrate that external auditors' perceptions of the ease of using artificial intelligence aids in enhancing audit quality. Similarly, gauging external auditors' perceived usefulness or benefits of artificial intelligence can also lead to improved audit quality. This study's sample is limited to external auditors of financial statements at public accounting firms, and therefore the findings should not be extended to other types of auditors such as government or internal auditors. This study offers external auditors a thorough comprehension of how artificial intelligence contributes to the audit process to improve audit quality. The necessity for external auditors to improve their technical skills arises due to the increased utilization of big data by businesses. Hence, universities must provide graduates with competence in not only accounting and auditing but also the latest technology.